Desmids from Bees-hazaar Lake, Chitwan, Nepal - Rai, Shiva Kumar; Rai, Ram Kumar; Paudel, N. (Our Nature, 2009)
A total 36 taxa belonging to 7 genera of desmids have been described and illustrated from Bees-hazaar lake of which 11 taxa are recorded for the first time for Nepal. This is a preliminary work on the desmids from this lake. Keywords: Algae, Bees-hazaar Lake, Desmids, Nepal. doi: 10.3126/on.v6i1.1656 Our Nature (2008)6:58-66